Rock 'n' roll party honoring Les Paul - Beck, Jeff (Rhino, 2011)
Jeff Beck, one of rock's most admired guitarists and two-time Rock and Roll Hall of Fame inductee, pays homage to musical pioneer and guitar icon Les Paul with an electrifying tribute concert from the Iridium Jazz Club in New York City.